A role for midcingulate cortex in the interruptive effects of pain anticipation on attention - Brown, Christopher A; Jones, Anthony KP (Clinical neurophysiology, 2008)
To investigate the anticipatory neural processes associated with the interruptive effects of pain anticipation on attention. Sustained attention was measured in healthy subjects ( n = 24) by the number of task errors in a go/no-go task involving temporal discrimination of non-painful cutaneous electrical stimuli. Painful distractors were randomly delivered to the same spatial location and the resulting increases in task errors (indicating interruption of attention) were measured. In a separate task the same subjects attended to the spatial location of painful laser stimuli delivered to the right forearm, and we localized the sources of anticipatory ERPs prior to stimulation. Pain anticipation was associated with activation of pain matrix areas including bilateral insula, mid- and posterior cingulate cortices, and bilateral inferior parietal cortices. Subjects with greater pain-related increases in task errors found the pain to be more unpleasant, and showed increased early pain-related anticipatory processing in the midcingulate cortex. They also demonstrated reduced processing in a spatial attention network comprising posterior cingulate and inferior parietal cortices. The results suggest a role for the midcingulate cortex in interrupting attention during pain anticipation. Individuals with greater anticipatory midcingulate responses may be predisposed to developing chronic pain and hypervigilance toward clinical pain symptoms.